Dynamic organization of lymphocyte plasma membrane: lessons from advanced imaging methods - Owen, Dylan M (Blackwell Science Inc, 2010)
Lipids and lipid domains are suggested to play an essential role in the heterogeneous organization of the plasma membrane in eukaryotic cells, including cells of the immune system. We summarize the results of advanced imaging and physical studies of membrane organization with special focus on the plasma membrane of lymphocytes. We provide a comprehensive up-to-date view on the existence of membrane lipid and protein clusters such as lipid rafts and suggest research directions to better understand these highly dynamic entities on the surface of immune cells.